Social and economic characteristics of AIDS patient in Jordan: A descriptive field study - Omar, Hussein; khozahe, Al (Advances in Social Sciences Research Journal, 2018)
This study aims to identify the status of AIDS patients in Jordan and their social and economic characteristics through detecting number of the cases and ways of contracting this disease. The patients were classified according to age, gender , place of contracting the disease, and their origin. The study came with the following results: The total number of the detected cases since the establishment of the national AIDS program for disease prevention in 1986 till the end of 2015 was 1222 cases; 325 Jordanian and 897 foreigners . The total number of deaths of this disease was 115. Having illegitimate sex contact is the first reason for AIDS infection( 55%); most of these cases were outside Jordan. the age categories (30-39) and (40-49) came first among AIDS patient (52%).Additionally, 20% of the AIDS patients were female and 26.6% of the total number of AIDS patients were Jordanians. The moment the disease is discovered, the AIDS patient feels shocked, denial and regret then he starts accepting it and integrating into society.